Network construction, evaluation and documentation: A guideline. (June 2021) - Scharler, U.M.; Borrett, S.R.
Abstract: Network analysis of complex systems is a rapidly growing field. Both theoretical and empirical network studies have permeated many different ecological, biological, social, and economic fields, investigating the interrelationships between nodes as structural and functional attributes in static, time-dynamic, or spatially explicit formats. We consider the network construction phase as a vital, but neglected component, and therefore provide recommended guidelines, describe how to evaluate the resulting network model quality, and highlight tools to assess their plausibility. Thereby we stress the importance of constructing multiple plausible networks to comply with basic scientific standards, and to pave the way for better informed evaluations. Finally, we provide recommendations for the management and policy arena where we advocate a thorough interrogation of network analyses outcomes (metrics) especially with regard to their sensitivity to the construction process, and a focus on relative changes between and within systems (e.g. as indication of vulnerability), rather than strict benchmarks. Highlights: A comprehensive guide for ecosystem and socio-economic network construction rooted in shared, collective and new practice. Construction of multiple plausible networks per system is necessary for scientific rigour and further robust analysis. Evaluation of constructed networks against both input data and plausibility are requisites. Sensitivity evaluation of analysis outcomes to the network construction process is imperative for research and applications.